PARALOLE IN PENITENTIARY SYSTEM VIEWED FROM THEORY OF DIGNIFIED JUSTICE - Tri Astuti Handayani (Surakarta Law and Society Journal, 2019)
The purpose of this study was to analyze how parole in terms of dignified justice. Type research uses normative legal research with the approach of legislation and approach to the concept. The data used is secondary data which comprise a source of primary law and secondary law material. The research results show that the granting of parole to prisoners intended that the inmate can be directly adapted himself to the public before the end of its life criminal. Granting parole intended for inmates to realize the error and the community to accept their presence in public life, useful and responsible